Multicultural and Education Religion Islam in building man Which have piety social - Fadli, Subhan (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
The purpose of Islamic education is to equip Muslims to be able to realize the essence of their creation as abid and caliph on earth, and to achieve the perfection of morals. This is in line with the purpose of Islam itself. Multicultural education can be said to be a response to the phenomenon of culture, social, and ethnic conflict that arises in the midst of a society based on multiculturalism. Multiculturalism is an understanding that accepts the existence of a pluralistic society so as to avoid horizontal conflicts that exist in society. The context of multicultural education only instills the rules of life such as respect, compassion, sincerity, and tolerance for the diversity of cultures that live in the midst of a plural society. The main purpose of multicultural education is to produce generations of people who have knowledge, skills and are able to apply life together in society as the best ummah/khoiru ummah.